Which Is The Fairest Between Civil Inheritance Law, Customary Inheritance Law or Islamic Inheritance Law? - Rachmat Trijono (Himmah: Jurnal Kajian Islam Kontemporer, 2019)
Basically, inheritance law is closely related to the scope of human life, because every human being will certainly experience a legal event called death. Inheritance law in Indonesia is very diverse, namely civil inheritance law, customary inheritance law, and inheritance law according to Islamic Teachings. The purpose of this research is to find out the fairest inheritance law, between civil inheritance law, customary inheritance law, or Islamic inheritance law. The problem under investigation is which one the fairest? The method that used in this research is qualitative method with a utility approach. The results showed that none inheritance law is fairest, civil inheritance law, customary inheritance law or Islamic inheritance law that fair. Everything is fair according to its usefulness. Civil inheritance law is fair if used for those who use it, Islamic inheritance law is fair to those who are Muslim and customary inheritance law is fair for those who apply it. The advice given is the application of inheritance law should be adjusted according to its usefulness. Keywords: Inheritance Law, Civil Inheritance Law, Customary Inheritance Law, Islamic Inheritance Law.